Compounding and the mechanical properties of catla fish scales reinforced-polypropylene composite–from biowaste to biomaterial. (3rd March 2020) - Aradhyula, Thirumala Vasu; Bian, Da; Reddy, A. Babul; Jeng, Yeau-Ren; Chavali, Murthy; Sadiku, E. R.; Malkapuram, Ramakrishna
Abstract : In this study, bio-waste catla fish scale (CFS) was used as a reinforcing agent in polypropylene (PP) for the fabrication of biomaterials by using a twin-screw extrusion technique. Tensile strength, elongation-at-break and heat deflection temperature (HDT) of the composites decreased upon the addition of CFS, however, Young's modulus improved, significantly. The flexural strength, density, and hardness of the composites increased by 5%, 1%, and 11%, respectively, with increasing the CFS content. The impact strength and the melt flow index (MFI) noticeably increased with increasing CFS loading. These results signified the fact that the CFS/PP composites from CFS biowaste showed improved mechanical properties and it can be a potential alternative biomaterial for various biomedical applications. In addition, the application of CFS as a filler in polymers can be viewed as a sustainable approach that incorporates biowaste-based value-added material and can simultaneously mit i gate the sewage problems in a smart manner in the marine environment.